PENGARUH ABU SEKAM PADI DAN PUPUK ZA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Della Zalfadyla; Hayatiningish Gubali; Zulzain Ilahude (Jurnal Lahan Pertanian Tropis (JLPT), 2022)
The decline in cayenne pepper crop production is partly due to low soil fertility. Efforts to increase crop production can be done by applying rice husk ash as a soil reformer combined with ZA fertilizer, so that plant nutrient needs are fulfilled. This study aims to determine the effect of applying rice husk ash and ZA fertilizer and their interactions on the growth and yield of cayenne pepper plants and to determine the dose of husk ash and ZA fertilizer that is suitable for the growth of cayenne pepper plants. This research was carried out in North Huntu Village, South Bulango District, Bone Bolango Regency, for four months starting from June to September 2021. This research use Factorial Group Randomized Design which consists of 2 factors. The first factor is rice husk ash which consists of three levels, namely 40, 50, and 60 g plant-1. The second one is ZA fertilizer with 3 levels, namely 10, 20, and 30 g plant-1. The observed parameters include plant height, number of productive branches, the weight of fruits, and the number of fruits. The data analysis uses analysis of variance (ANOVA) with a 5% BNT test. The results showed that rice husk ash and ZA fertilizer affected the growth and yield of cayenne pepper plants. The best results are obtained with the application of husk ash at a dose of 60 g plant-1 and ZA fertilizer at 30 g plant-1.Keywords: Rice husk ash, ZA fertilizer, cayenne pepper